Attending to political conflict in social work today and in the near future - Ramon, Shula (Socialno delo, 2021)
This paper is aimed at looking at how social workers in Europe tackle the inevitable political issues embedded in their work as intermediaries between political authorities (governments and local authorities) and social work clients affected by political conflict. The notion that social work can be a-political is rejected from the outset. The outcomes of armed political conflict for the populations involved, as well as for social workers who are citizens in these countries, and who remain in their country of origin, are briefly looked at. The migration wave of 2015-2017 and its aftermath is used as the key example with which to explore further the issue of clash between social work values and those of the majority of the European member states governments. Key changes taking place since 1980s in political ideologies of these states, including the issues of nationalism alongside neoliberalism and imposed changes in the welfare state which reveal going back to pre 2nd World War perception of poor, disabled, and destitute people are examined. The impact of these changes on attitudes towards refugees, asylum seekers and migrants are investigated. Some key examples of social workers attempting to change the worsening situation for their clients are given. The paper ends in considering the options for social workers wishing to follow the values of social work in their collective and individual practice.
Keywords: asylum seekers; authoritarianism; avtoritarianizem; begunci; illiberal state; migracije; migration; neliberalna država; prosilci za azil; refugees; socialni sistemi; welfare systems